Association of Maternal Zinc Status and Fetal Outcome - Rahman, Md Habibur; Hoque, Mozammel; Jahan, Waseka Akhter; Hassan, Zaheed; Shakoor, MA; Begum, Bilqis Ara; Sultan, Md Kamal (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Maternal zinc is related to the growth and development of newborn babies. Low birth weight babies leads to higher infant mortality rate & unfortunately the incidence of LBW is higher in Bangladesh. Objective: The present study has been undertaken to evaluate the zinc status in mothers with normal and low birth weight as well as to find-out the association between maternal zinc level and birth weight of babies in a selected hospital in Dhaka city. Methods: This case-control study on 20 non-pregnant and 40 pregnant women was done to find out the relationship between maternal zinc status and fetal outcome. This study was carried out in the department of Biochemistry, Dhaka Medical College, Dhaka, in collaboration with Bangladesh Atomic Energy Center, Dhaka from the period of July 2003 to June 2004. Result: The mean age (yrs), height (cms) & parity (number) in Group-A found to be 23.7 ± 4.8, 154 ± 7 and 1.82 ± 0.85 respectively & those in Group-B were 24.5 ± 4.3, 153 ± 9 and 1.86 ± 0.89 respectively without any significant difference between the groups. The mean plasma zinc concentrations in Control & Cases were 90.10 ± 13.96 and 64.54 ± 16.22 ?g/dl respectively. The mean plasma zinc concentrations in Subgroup B-I & B-II were 63.85 ± 12.49 and 65.18 ± 18.48 ?g/dl respectively. Conclusion: Maternal zinc status is not associated with fetal outcomes. J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 7-10